Relationship Between Systemic Immune-Inflammation Index and Irritable Bowel Syndrome - Güven, İbrahim Ethem and Başpınar, Batuhan and Atalay, Roni (Turkish Journal of Gastroenterology, 2022)
Background: Irritable bowel syndrome is accepted as a functional disorder; however, there is growing evidence in favor of the inflammatory process contributing to its pathogenesis. We aimed to evaluate the role of the systemic immune-inflammation index as a marker of inflammation in patients with irritable bowel syndrome. Methods: The study was conducted in the outpatient clinic of the Gastroenterology Department with patients having constipationpredominant irritable bowel syndrome diagnosis according to Rome IV criteria between March 1, 2019 and December 31, 2020. The systemic immune-inflammation index was calculated and compared with age- and sex-matched healthy controls. Results: The study was performed with 214 participants, 107 patients and 107 control groups. Platelet and neutrophil counts (P < .001, for both) were higher, and lymphocyte count (P = .003) was lower in the irritable bowel syndrome group. The systemic immune-inflammation index was higher in irritable bowel syndrome patients (P < .001). Multivariate logistic regression analyses showed the role of the systemic immune-inflammation index as an independent predictor of the presence of IBS (odds ratio: 1.100, P < .001). Conclusion: Systemic immune-inflammation index may be a cheap, universal, and reliable indicator of the inflammatory process in irritable bowel syndrome patients.